The foraminifera boogie - Holm, Villads; Losleben, Lisa Katrin; Zimmermann, Heike Jane; Clerici, Monica; Panieri, Giuliana (Septentrio Educational, 2023)
Focus: To learn about foraminifera through practicing and presenting the song “The Foraminifera Boogie”. Pupils and teachers can also decide to play instruments along with the recorded soundtrack. Learning objectives: In this activity, pupils will practice listening to one another and the music. They will learn lyrics and use their voices to sing the song. This can be combined with playing actual musical instruments or using instruments the pupils have made themselves (for example see the activity “Cold Seeps Symphony”). This activity brings together music with the scientific story of the Foraminifera. Key words: Ocean, researchers, little known beings in the Arctic Ocean, co-living of humans and non-human beings, planetary time.